Biological analyses of the effects of TiO2 and PEG-b-PLA nanoparticles on three-dimensional spheroid-based tumor - Koňariková, Katarina; Girašková, Gabriela Mária; Žitňanová, Ingrid; Dvořáková, Marcela; Rollerová, Eva; Scsuková, Soňa; Bizik, Jozef; Janubová, M; Muchová, Jana (Physiological research, 2023)
The aim of our study was to monitor the antiproliferative/ cytotoxic and genotoxic effects of both, poly(ethylene glycol)-block-poly(lactic acid) (PEG-b-PLA) and titanium dioxide (TiO2) nanoparticles on the tumor (HT-29, MCF-7, U118MG) and healthy (HEK-293T) cell lines during 2D cultivation and during cultivation in the spheroid form (3D cultivation). Cells or spheroids were cultivated with nanoparticles (0.01, 0.1, 1, 10, 50, and 100 ?g/ml) for 72 hours. The cytotoxic effect was determined by the MTT test and the genotoxic effect by the comet assay. We found that 2D cultivation of tumor cell lines with PEG-b-PLA and TiO2 nanoparticles had an anti-proliferative effect on human colon cancer cell line HT-29, human breast cancer cell line MCF-7, human glioma cell line U-118MG during 72h cultivation, but not on control/healthy HEK-293T cells. At the concentrations used, the tested nanoparticles caused no cytotoxic effect on tumor cell lines. Nanoparticles PEG-b-PLA induced significant damage to DNA in HT-29 and MCF-7 cells, while TiO2 nanoparticles in MCF-7 and U-118MG cells. Only PEG-b-PLA nanoparticles caused cytotoxic (IC50 = 7 mikrog/ml) and genotoxic effects on the healthy cell line HEK-293T after 72h cultivation. The cells which were cultivated in spheroid forms were more sensitive to both types of nanoparticles. After 72h cultivation, we observed the cytotoxic effect on both, the tumor and healthy cell lines.
Keywords: Polyesters; Nanoparticles; Polyethylene Glycols; polyethylenglykoly; lidé; Antineoplastic Agents; protinádorové látky; polyestery; Cell Line, Tumor; nádorové buněčné linie; nanočástice; Humans